SOME THOUGHTS ON ECONOMY WITHIN LINGUISTICS - Uriagereka, Juan (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
One of the cornerstones of Chomsky’s Minimalist Program is the role played by economy. This paper discusses different ways in which Chomsky’s notion of economy in linguistics can be understood, given current views on dynamic systems and, in particular, on evolution in biological systems